Cooperative Finite-time Control for autonomous vehicles platoons with nonuniform V2V communication delays. Issue 36 (2022) - Caiazzo, Bianca; Lui, Dario Giuseppe; Petrillo, Alberto; Santini, Stefania
Abstract: In this paper we introduce a novel fully distributed finite-time cooperative control law able to solve the platoon formation control problem for a network of autonomous vehicles, whose dynamics is represented via the third-order drivetrain linear model. Internet of Vehicle (IoV) communication latencies have been considered and modeled via heterogeneous time-varying delays. The resulting control protocol is computed via outdated information and embeds vehicles acceleration error, which allows improving control reactivity during sudden acceleration/deceleration maneuvers. The finite-time stability of the vehicular network has been analyzed and proved by leveraging Multi-Agent Systems (MASs) paradigm along with Lyapunov-Krasovskii method. This latter leads to stability conditions in the forms of Linear Matrix Inequalities, whose solution allows finding control gains and state trajectories threshold. Simulation results confirm the effectiveness of the theoretical derivation in guaranteeing the cooperative driving despite the presence of IoV communication latencies.